Efektivitas layanan informasi dengan menggunakan metode blended learning untuk meningkatkan motivasi belajar - Emria Fitri; Ifdil Ifdil; Neviyarni S. (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
This study aimed to identify the effectiveness of  layanan informasi using blended learning methods to improve students' motivation. The study used a quasi-experimental design types of non equivalent control group. Sampling using purposive sampling with sample 22 in the experimental group and 23 control group. The instrument uses Pengukuran Motivasi Belajar Scale (SPMB). The study findings revealed that 1) the level of student motivation experimental group in the pretest middle category while, at posttest at the high category, 2) the level of student motivation control group at pretest and posttest same which are in the moderate category, 3) there is a difference significant student motivation experimental group before and after treatment of information services using blended learning methods, 4) there is a significant difference in students' motivation experimental group treated with the information service blended learning method with the control group. Based on these results it can be concluded that the service information using blended learning methods effectively improve students' motivation.